Romanian Management Theory and Practice Navigating Digitization and Internationalization in the New Global Economy - Nicolescu, Ovidiu; Oprean, Constantin; Titu, Aurel Mihail; Vaduva, Sebastian; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book provides the current research on the features of Romanian management theory and practices. It explores Romania$1 (Bs position in the global supply chain; Romanian firm$1 (Bs contributions to the new global economy; and the processes and effect of internationalization and digitization on the Romanian economy. Romanian management practices, similar with other Eastern European nations, has a unique development. In the late 19th and early 20th century, they were an integral part of western management thinking. However, with the forced adoption of a communist political system and the nationalization of the Romanian economy, the managerial systems were recalibrated to replace profit maximizing objectives with social objectives yielding mixed results. Since the revolution of 1989 and the integration into NATO and the European Union, Romanian management systems are once again an integral part of the global economy. As the COVID-19 crisis revealed the limitations of globalization and the overreliance on Asian suppliers, Romania, along with the rest of Eastern Europe will continue to be integrated into the global economy and become a dependable alternative to Asian suppliers. This is an open access book.s
An Analyses on the Environment Structure Strategy and Performance A Bibliometric Perspective -- The Culture of Quality and the Organizational Behavior of Knowledge Organizations in The COVID Context -- Stakeholders Based Management A Company Relevant Alternative -- Aggregate Planning for Services Challenges and Opportunities -- Barriers to Integrated Risk Management Services within Health Insurance in Central and Eastern Europe -- The Virtuous Innovation Internationalization Performance Circle Evidence from The Romanian ICT Sector -- Modern Instrument for Nonconformities Management Within Quality Management Systems -- Urban Management for a Green Transition -- Importance of teamwork and analysis of employer employee relationship in the COVID19 context -- A Humanistic Approach to Recommender Systems Implications for 5 Marketing Management -- Adapting Strategies of Portfolio Management to VUCA Environments The case of Romania -- Career Shocks of Women in Leadership Positions in Romania -- Enhancing Well Being Education Through Innovative Management.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Strategic planning; Leadership; International economic integration; Globalization; Europe -- Economic conditions; Business Strategy and Leadership; Emerging Markets and Globalization; European Economics